2021
DOI: 10.47268/sasi.v27i1.419
|View full text |Cite
|
Sign up to set email alerts
|

Model Perlindungan Dan Pengelolaan Lingkungan Hidup Dalam Mewujudan Good Governance

Abstract: This research is a research that aims to identify and examine the application of authority related to environmental management in Way Kanan Regency and to find a model of good environmental supervision and management in the district by the Environment Agency in realizing good governance. The method used in this study is a normative-empirical research method using a statute approach and in-depth interviews. The findings of this study are that the implementation of the authority of the environmental services in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
2
0
2
Order By: Relevance
“…Sehingga pemerintah wajib menjaga agar kondisi lingkungan hidup. Pengelolaan lingkungan hidup yang dilaksanakan secara optimal sesuai kewenangan, dapat mempengaruhi tercapainya kesuksesan pengelolaan lingkungan dan sumber daya alam (Prastyo, et al, 2021). Salah satu komponen lingkungan hidup yang harus dijaga kondisinya dari kerusakan dan pencemaran adalah udara.…”
Section: Pendahuluanunclassified
“…Sehingga pemerintah wajib menjaga agar kondisi lingkungan hidup. Pengelolaan lingkungan hidup yang dilaksanakan secara optimal sesuai kewenangan, dapat mempengaruhi tercapainya kesuksesan pengelolaan lingkungan dan sumber daya alam (Prastyo, et al, 2021). Salah satu komponen lingkungan hidup yang harus dijaga kondisinya dari kerusakan dan pencemaran adalah udara.…”
Section: Pendahuluanunclassified
“…4 Pendekatan statute approach yaitu mengkaji hal-hal yang menyangkut asas-asas hukum, pandangan dan doktrin-doktrin hukum, dan peraturan perundang undangan terkait lahan pertanian berkelanjutan, dan data yang akurat serta dapat dipertanggung jawabkan kebenaranya. 5 Selain itu juga diadakan pemeriksaan mendalam terhadap fakta hukum tersebut untuk kemudian mengusahakan pemecahan atas permasalahan yang timbul didalam gejala yang bersangkutan. 6 Data dianalisis menggunakan konten analisis.…”
Section: B Metode Penelitianunclassified
“…State of the art in this article, first, research result by Agung Budhi Prastyo, et.al., showed that the less optimal supervision of Environmental Governance Body in Way Kanan Municipality, caused the environmental damage, but the model of implementation of principle of good environmental governance was maximum implemented [2]. Second, research result by Umi Mustagfiroh, et.al, showed that some municipality in Indonesia, already implemented the principle of good environmental governance in garbage management system by public participation and the system itself [3].…”
Section: Introductionmentioning
confidence: 99%